2021
DOI: 10.1051/e3sconf/202129803007
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and growth coupling during different development larvae phases of the Mediterranean mussel Mytilus galloprovincialis L. from Amsa Bay

Abstract: Spat supply for mussel farming in Morocco is essentially based on seed capture and collection from natural beds. However, natural irregularity recruitment in exploited areas and encountered difficulties during spat collection operations have led to develop and improve reproduction techniques under controlled conditions in hatcheries. The present study focused on the larvae phase aiming at assessing growth rate varies between different development stages. Trocophore larva stage had a size of 63.25 μm and reache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Those studies have revealed a high potential innovation in mussel aquaculture development [32], especially to produce juveniles and reduce pressure on natural populations [33]. It is well known that mussel larval rearing is directly influenced by temperature [34], feeding regimes [35][36][37], stocking density [38,39], bacterial loads [40] and CO 2 levels [41], all of which improve or worsen the final larvae performance. Irreversible physiological processes in the pediveliger larvae of bivalves lead to the transition from planktonic to benthic life throughout metamorphosis and settlement [42].…”
Section: Introductionmentioning
confidence: 99%
“…Those studies have revealed a high potential innovation in mussel aquaculture development [32], especially to produce juveniles and reduce pressure on natural populations [33]. It is well known that mussel larval rearing is directly influenced by temperature [34], feeding regimes [35][36][37], stocking density [38,39], bacterial loads [40] and CO 2 levels [41], all of which improve or worsen the final larvae performance. Irreversible physiological processes in the pediveliger larvae of bivalves lead to the transition from planktonic to benthic life throughout metamorphosis and settlement [42].…”
Section: Introductionmentioning
confidence: 99%